”Kehittyvä ammattikunta, jolla on potentiaalia olla tärkeässä roolissa” : osteopaattien käsityksiä itsestään kuntoutusalan ammattilaisina Suomessa - Honkanen, Tero (2024)
Osteopathy is classified as a manual treatment modality in the field of medical rehabilitation and one of the professions that form the field of rehabilitation in Finland. In previous studies conceptions of osteopaths have been researched in international context. The aim of this Master’s thesis was to produce qualitative information about osteopaths’ conceptions of themselves as professionals in the field of rehabilitation in Finland.